Regulatory Innovations and Policy Options for Synthetic Media and Digital Democracy - McIntyre, Andrew; Yousefi, Yasaman; Sánchez Galera, María Dolores (Deepfakes, Democracy, and the Ethics of Synthetic Media: A Synthesis of the SOLARIS Project, 2026)
This chapter explores potential regulatory innovations and policy options for addressing the democratic risks and opportunities of AI-generated content (AIGC) within the European context. Drawing upon and responding to discussions in previous chapters, it argues that current policy approaches centred on the detection, moderation and containment of AIGC are not only insufficient but also risk reinforcing authoritarian tendencies. Instead, the chapter outlines a policy strategy that emphasizes political participation and pluralism as a means of promoting democratic resilience and addressing the specific harms of AIGC. This strategy is oriented around three key objectives: (i) clarifying AIGC harms, (ii) strengthening institutional coordination, and (iii) enhancing digital literacy and citizenship. Key to this strategy is the reconceptualization of generative AI as a creative and expressive tool for promoting more inclusive political dialogue and democratic debate. Ultimately, this chapter envisions a future in which GenAI is not solely understood as a threat to democracy but as a resource for fostering a more trustworthy information environment and political system. It is a future where truth may become increasingly difficult to determine, but in which our democratic values nonetheless remain protected and strengthened.